Frontispiece: Betaine and Carnitine Derivatives as Herbicidal Ionic Liquids. Issue 34 (9th August 2016) - Pernak, Juliusz; Niemczak, Michał; Chrzanowski, Łukasz; Ławniczak, Łukasz; Fochtman, Przemysław; Marcinkowska, Katarzyna; Praczyk, Tadeusz
Abstract : Plant Protection Herbicidal ionic liquids (HILs) are organic salts based on commonly used herbicides, which are characterized by high efficacy against weeds and limited volatility. Two amino acid derivatives, betaine and carnitine, were used as cations of natural origin in order to achieve low toxicity and enhanced biodegradability. The compounds reported in the Full Paper by J. Pernak and colleagues onpage 12012 ff. may be a promising alternative to commercial herbicidal formulations due to their favourable physicochemical properties and low environmental impact.